2021
DOI: 10.1111/jpc.15786
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and outcomes of SARS‐CoV‐2 infection in Victorian children at a tertiary paediatric hospital

Abstract: Aim: Victoria experienced two 'waves' of COVID-19 between March and September 2020 and more cases than any other jurisdiction in Australia. Although world-wide reports of COVID-19 reflect that children are less likely to experience severe disease compared with adults, hospitalisations and deaths have been reported. We report testing and outcomes of children with SARS-CoV-2 infection presenting to a tertiary paediatric hospital in Melbourne. Methods: We conducted a prospective cohort study at The Royal Children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 23 publications
0
9
0
2
Order By: Relevance
“…Our findings are consistent with overseas evidence that a large proportion of SARS‐CoV‐2 infections in children are asymptomatic, and that clinical illness in those who develop symptoms is typically mild. 2 , 15 This reassuring finding suggests that we need to carefully consider both the harms of infection and those caused by population‐level shielding of children from infection, which could be considered as disproportionate with respect to disease risk, although the long term effects of infection are still poorly characterised. 16 Why COVID‐19 is less severe in children than adults is unclear, but a number of explanations have been proposed, including altered expression and affinity of SARS‐CoV‐2‐binding receptors, and more effective innate immunity in the upper airways.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our findings are consistent with overseas evidence that a large proportion of SARS‐CoV‐2 infections in children are asymptomatic, and that clinical illness in those who develop symptoms is typically mild. 2 , 15 This reassuring finding suggests that we need to carefully consider both the harms of infection and those caused by population‐level shielding of children from infection, which could be considered as disproportionate with respect to disease risk, although the long term effects of infection are still poorly characterised. 16 Why COVID‐19 is less severe in children than adults is unclear, but a number of explanations have been proposed, including altered expression and affinity of SARS‐CoV‐2‐binding receptors, and more effective innate immunity in the upper airways.…”
Section: Discussionmentioning
confidence: 99%
“…We found that medical hospitalisation was more common for children who had other medical conditions, consistent with other reports. 2 , 3 , 18 Immunodeficiency was recorded for few children admitted to hospital; eight of 14 children admitted to intensive care had overweight, an important risk factor for severe COVID‐19 in adults and children, 19 but this factor was not included in our multivariable model because individual weight data were not available for children receiving virtual care. Non‐asthmatic respiratory disease was associated with greater likelihood of hospitalisation, but not asthma/viral induced wheeze, as also found by other investigators.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations